Enuma Elish dan Narasi Penciptaan Kitab Kejadian: Analisis Komparatif dalam Konteks Timur Dekat Kuno - Hendra Dinata; Ledi Arlinda Ompusunggu; Penulis Ketiga (Sekolah Tinggi Teologia Kerusso Indonesia, 2025)
This study aims to examine the Enuma Elish as a cultural background for the creation narrative in the Book of Genesis within the context of the Ancient Near East. The research employs a library-based method with a descriptive-comparative approach and a rational, critical analysis of various scholarly perspectives on the relationship between Babylonian mythology and the biblical narrative. The findings indicate several thematic parallels between the Enuma Elish and the creation narrative in Genesis, particularly in their depictions of the primordial condition of the cosmos and the origin of the world. However, comparative analysis reveals fundamental theological differences between the two texts. The Enuma Elish portrays the creation of the world through conflicts among gods within a polytheistic belief system, whereas the Book of Genesis affirms that the world was created by the one sovereign God through His word in an orderly manner. This distinction is also evident in the understanding of humanity, which in Genesis is presented as created in the image of God (imago Dei). Therefore, the thematic similarities between the two texts are more appropriately understood as reflections of a shared cultural context in the Ancient Near East rather than as evidence of direct dependence of the Genesis narrative on Babylonian mythology.